Distinguishing Ventricular Arrhythmia Originating from the Right Coronary Cusp, Peripulmonic Valve Area, and the Right Ventricular Outflow Tract: Utility of Lead I. (8th January 2014) - EBRILLE, ELISA; CHANDRA, VISHNU M.; SYED, FAISAL; DEL CARPIO MUNOZ, FREDDY; NANDA, SUDIP; HAI, JO JO; CHA, YONG‐MEI; FRIEDMAN, PAUL A.; HAMMILL, STEPHEN C.; MUNGER, THOMAS M.; VENKATACHALAM, K.L.; PACKER, DOUGLAS L.; et al.
ECG Lead I and Outflow Tract Arrhythmia: Introduction: Outflow tract ventricular arrhythmia (OTVA) can be complicated to target for ablation when originating from either the periaortic or pulmonary valve (PV) region. Both sites may present with a small R wave in lead V1. However, the utility of lead I in distinguishing these arrhythmia locations is unknown. Methods and Results: Thirty‐six consecutive patients (mean age 41 ± 14 years, 13 male) underwent catheter ablation for OTVA. OTVA origin was determined from intracardiac electrogram tracings and electroanatomic maps. Observers blinded to results measured QRS waveform amplitude and duration from standard 12‐lead ECG tracings. Measurements with highest diagnostic performance were modeled into an algorithm. Sites of successful ablation were anterior right ventricular outflow tract (RVOT; n = 6), posterior RVOT (n = 4), PV (n = 18), and right coronary cusp (RCC; n = 8). Highest performing surface ECG discriminators were from lead I to V1 vectors: RCC, lead I R wave ≥ 1.5 mV, and V1 R wave ≥2.0 mV (sensitivity 87%, specificity 93%); PV, V1 R wave > 0 mV, and lead I R/(R+S) ≤ 0.75 (sensitivity 78%, specificity 72%); anterior RVOT, V1 R wave = 0 mV, and lead I R/(R+S) <0.4 (sensitivity 67%, specificity 97%); posterior RVOT, V1 R wave > 0 mV, and lead I R/(R+S) > 0.75 (sensitivity 75%, specificity 84%). Sequential algorithmic application of these criteria resulted in an overall accuracy of 72% in predicting site of OTVA origin. Conclusions: A relatively large R wave in lead I is seen with RCC origin but not PV origin. A sequential algorithm has limited but potentially significant value beyond assessment of lead I in approaching OTVA.